Evaluation of temperament information to improve adoption occurrence and evaluation of human contact and housing arrangement on stress response of adult shelter dogs - Coppola, Crista L., author (Colorado State University. Libraries, 2004)
A high proportion of dogs will spend an indeterminate period of time in an animal shelter, either waiting to be claimed by their owner; waiting to be adopted or waiting to be euthanized. For a dog, an animal shelter is an extremely stressful environment. An animal shelter incorporates two of the main psychological stressors for dogs, lack of social contact and novel, unpredictable surroundings. This study was designed to determine if adoption numbers, time to adoption and adoption satisfaction could be improved through the utilization of available temperament information. This study also examined factors affecting stress response, as measured by salivary cortisol. The adoption experiment involved 88 adult, stray dogs available for adoption (48 treatment and 40 control). The treatment dogs were made available for adoption with name, approximate age, sex and applicable temperament information accessible to the general public. Control dogs were available for adoption with name, approximate age, sex and estimated breed(s) information accessible. Treatment dogs were adopted more often and more quickly (P= 0.036 and 0.033, respectively) than control dogs. Sixty-three percent of the treatment dogs were adopted in an average of 5.64 days while only thirty-seven percent of the control dogs were adopted in an average of 7.05 days. The same animals were utilized in a second experiment to determine the effect of human contact on stress response. The treatment dogs from the first experiment engaged in a 30-45 minute human contact session on the second day after arrival to the shelter while control dogs did not engage in a scheduled human contact session. There was a considerable difference in stress response measured on day 3 between the two groups (P= 0.014). Treatment dogs' cortisol level was 36% lower than the control dogs on day 3. The third experiment examined the effect of pair housing on stress response. This experiment utilized 54 adult shelter dogs that had been housed in the shelter for at least nine days. The dogs were housed either alone or with another dog in identical kennels in the same adoption area. Dogs housed alone had numerically higher cortisol levels than dogs housed in pairs but no significant differences were detected (P> 0.05). Based on these results, it was concluded that the adoption process could be improved by providing temperament information and stress response could be reduced when human interaction is implemented on the second day of housing in the shelter.